Disease Specific Aspects of Malnutrition in Neurogeriatric Patients - Prell, Tino; Perner, Caroline (Frontiers in Aging Neuroscience, 2018)
Malnutrition in elderly patients is a common condition. Nevertheless, there is evidence on specific risk factors and problems of malnutrition in geriatric patients with neurological diseases. In this review, we summarize recent knowledge on malnutrition in different neurological diseases with a focus on elderly patients. This overview also provides strategies for a more specific and profound assessment of neurogeriatric patients to improve identification and treatment of malnutrition. Early and consequent treatment of malnutrition can lead to a decreased progression of the neurological disease and to a better quality of life in geriatric patients.